we.b: The web of short URLs - Antoniades, Demetris; Polakis, Iasonas; Athanasopoulos, Elias; Ioannidis, Sotiris; Markatos, Evangelos P.; Karagiannis, Thomas (20th International World Wide Web Conference (WWW 2011), 2011)
Short URLs have become ubiquitous. Especially popular within social networking services, short URLs have seen a significant increase in their usage over the past years, mostly due to Twitter’s restriction of message length to 140 characters. In this paper, we provide a first characterization on the usage of short URLs. Specifically, our goal is to examine the content short URLs point to, how they are published, their popularity and activity over time, as well as their potential impact on the performance of the web. Our study is based on traces of short URLs as seen from two different perspectives: i) collected through a large-scale crawl of URL shortening services, and ii) collected by crawling Twitter messages. The former provides a general characterization on the usage of short URLs, while the latter provides a more focused view on how certain communities use shortening services. Our analysis highlights that domain and website popularity, as seen from short URLs, significantly differs from the distributions provided by well publicised services such as Alexa. The set of most popular websites pointed to by short URLs appears stable over time, despite the fact that short URLs have a limited high popularity lifetime. Surprisingly short URLs are not ephemeral, as a significant fraction, roughly 50%, appears active for more than three months. Overall, our study emphasizes the fact that short URLs reflect an “alternative” web and, hence, provide an additional view on web usage and content consumption complementing traditional measurement sources. Furthermore, our study reveals the need for alternative shortening architectures that will eliminate the non-negligible performance penalty imposed by today’s shortening services.